How Huawei Succeeds in Africa: Training and Knowledge Transfers in Kenya and Nigeria - Henry Tugendhat (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
Dive into some of the keys behind Chinese Huawei's success in Henry Tugendhat's latest policy brief. Tugendhat describes how the Chinese giant in the Original Equipment Manufacturing (OEM) sector is taking Africa, specifically Kenya and Nigeria, by storm. By carefully balancing between training local engineers and keeping control of its intellectual property, Huawei moves forward transferring knowledge to local populations.
Keywords: 330